2022
DOI: 10.1108/ijwis-02-2022-0044
|View full text |Cite
|
Sign up to set email alerts
|

Fake news detection on Twitter

Abstract: Purpose Owing to the increased accessibility of internet and related technologies, more and more individuals across the globe now turn to social media for their daily dose of news rather than traditional news outlets. With the global nature of social media and hardly any checks in place on posting of content, exponential increase in spread of fake news is easy. Businesses propagate fake news to improve their economic standing and influencing consumers and demand, and individuals spread fake news for personal g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Lee et al [27] selected 21 features from the data stream and converted each feature in the network traffic data to 0 or 1 using a bitmap rule, dividing them into normal traffic or attack according to the range of feature values, thereby reducing the size and dimension of the data. Feature representation methods based on deep learning not only develop rapidly in the field of network attack detection, but also become the main method of feature representation in other research fields [28,29].…”
Section: Feature Extraction and Representation On Trafficmentioning
confidence: 99%
“…Lee et al [27] selected 21 features from the data stream and converted each feature in the network traffic data to 0 or 1 using a bitmap rule, dividing them into normal traffic or attack according to the range of feature values, thereby reducing the size and dimension of the data. Feature representation methods based on deep learning not only develop rapidly in the field of network attack detection, but also become the main method of feature representation in other research fields [28,29].…”
Section: Feature Extraction and Representation On Trafficmentioning
confidence: 99%
“…Results of their study showed that their ensemble model achieved an accuracy of 77.30%. For their parts, Sharma et al [29] opted for the same grouping method to classify fake tweets using a combination of ML with XGBoost classifier. This method obtained an accuracy of 81% on FakeNewsNet dataset that contains tweets with user characteristics.…”
mentioning
confidence: 99%